Interactions between Obesity Status and Dietary Intake of Monounsaturated and Polyunsaturated Oils on Human Gut Microbiome Profiles in the Canola Oil Multicenter Intervention Trial (COMIT) - Pu, Shuaihua; Khazanehei, Hamidreza; Jones, Peter J.; Khafipour, Ehsan (Frontiers in Microbiology, 2016)
Long-term dietary fatty acid intake is believed to induce changes in the human gut microbiome which might be associated with human health or obesity status; however, considerable debate remains regarding the most favorable ratios of fatty acids to optimize these processes. The objective of this sub-study of a double-blinded randomized crossover clinical study, the canola oil multi-center intervention trial (COMIT), was to investigate effects of five different novel oil blends fed for 30 days each on the intestinal microbiota in 25 volunteers with risk of metabolic syndrome. The 60 g treatments included three MUFA-rich diets: 1) conventional canola oil (Canola); 2) DHA-enriched high oleic canola oil (CanolaDHA); 3) high oleic canola oil (CanolaOleic); and two PUFA-rich diets: 4) a blend of corn/safflower oil (25:75) (CornSaff); and 5) a blend of flax/safflower oil (60:40) (FlaxSaff). Stool samples were collected at the end of each period. DNA was extracted and amplified for pyrosequencing. A total of 17 phyla and 187 genera were identified. While five novel oil treatments failed to alter bacterial phyla composition, obese participants produced a higher proportion of Firmicutes to Bacteroidetes than overweight or normal weight groups (P = 0.01). Similarly at the genus level, overall bacterial distribution was highly associated with subjects’ body mass index (BMI). Treatment effects were observed between MUFA- and PUFA-rich diets, with the three MUFA diets elevating Parabacteroides, Prevotella, Turicibacter, and Enterobacteriaceae (F)’s populations, while the two PUFA-rich diets favored the abundance of Isobaculum. High MUFA content feedings also resulted in an increase of Parabacteroides and a decrease of Isobaculum in obese, but not overweight subjects. Data suggest that BMI is a predominant factor in characterization of human gut microbiota profiles, and that MUFA-rich and PUFA-rich diets impact the composition of gut microbiota at lower taxonomical levels mainly in obese subjects.